Radiographic Union of Evans Osteotomy Without Fixation. Issue 4 (22nd October 2020) - Miles, Megan R.; Gallagher, Brian P.; Mistretta, Katherine L.; Hsu, Nigel N.; Wang, Haijun; Guyton, Gregory P.
Category: Hindfoot; Other Introduction/Purpose: The Evans osteotomy is a lateral column lengthening procedure of the calcaneus that is commonly used to correct flexible flatfoot deformities. There is no consensus on whether fixation is needed to avoid nonunion and calcaneocuboid subluxation when performing this osteotomy. We assessed the nonunion rate and correlated extent of subluxation with graft size in an unfixed Evans osteotomy with an allograft wedge and no pinning of the calcaneocuboid joint at any point in the largest series of the procedure to date. Surgeries were performed in patients undergoing flexible flatfoot reconstruction. Methods: We retrospectively reviewed 120 consecutive patients who had undergone 145 unfixed Evans osteotomies by a single surgeon with allogenic bone graft for flatfoot reconstruction between January 2013 and October 2017, with a mean follow-up of 62.5 (range 9.4-266.7) weeks. The calcaneocuboid joint was not pinned during the procedure. Data were collected using clinical and radiographical examination during regular follow-up. Results: A total of 137 feet (94.5%) underwent a double calcaneal osteotomy with an associated medial displacement calcaneal osteotomy (MDCO). There was one nonunion (0.69%). The mean time to union was 10.8 (range, 6.7-17.9) weeks. There was significant improvement in all radiographic parameters postoperatively, including calcaneal pitch, talonavicular uncoverage, anteroposterior and lateral talo-first metatarsal angle, lateral column length, and naviculocuboid overlap (p<0.05). Minor postoperative calcaneocuboid joint subluxation (1.51 +- 2.3 mm) occurred in 72 of 118 feet (61.0%) and had no correlation with wedge size (r=0.06; 95% CI, -0.13, 0.24; p=0.6). Conclusion: An unfixed Evans osteotomy for symptomatic flatfoot deformity resulted in a significant improvement in the radiographic alignment of the foot with an exceptionally rare nonunion rate. Detectable calcaneocuboid subluxation was common but minimal in extent and was not correlated with wedge size in this series in which wedges were less than 12 mm in the maximum dimension. This report represents the largest series of the Evans procedure to date.